African economic development - Nnadozie, Emmanuel U.; Jerome, Afeikhena (Emerald Publishing Limited, 2019)
When it was published in 2002, the first edition of African Economic Development offered an authoritative statement about economic growth on the continent. Its multidisciplinary regional studies built an analytic framework that served as a cornerstone of the field for over a decade. The second edition offers a new collection of authoritative articles for a new age. In a sweeping survey of African economies, leading scholars offer the latest research into the biggest current influences on African growth and development, taking account of relevant institutional contexts as well as significant or unique problems that have slowed Africa's progress. Despite recognizing the factors that have resulted in underdevelopment, however, the contributors paint a hopeful picture of the efforts being made to overcome barriers, and they suggest that a significant reduction of poverty is possible in the near future. Each chapter singles out a particular problem-be it related to demography, geography, politics, climate change, agriculture, or industrialization-and proposes pragmatic solutions that put Africans' needs and capabilities first. Balancing theory and empiricism, and eschewing vague ideological or political language, this book provides an important vantage point from which to herald Africa's elusive dawn. For its rigorous scholarship, its unique breadth, and its actionable suggestions for the near future, the second edition of African Economic Development is a must-read for students, researchers, and practitioners of international development.